1992
DOI: 10.1002/j.1460-2075.1992.tb05546.x
|View full text |Cite
|
Sign up to set email alerts
|

Epimutation of repeated genes in Ascobolus immersus.

Abstract: Ascobolus immersus artificial gene repeats were shown previously to be subject premeiotically to both cytosine methylation and inactivation. We studied sexual progenies of strains harbouring two wild type copies of the endogenous met2 gene lying either in tandem array or at ectopic unlinked positions, by (i) investigating the methylation status, (ii) searching for mutations and (iii) analysing the inheritance of inactivation both in mitotic and sexual offspring. 100% of the ‘tandem’ progeny and 64% of the ‘ect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 29 publications
2
86
0
1
Order By: Relevance
“…The present results can be related to the observation in higher eucaryotes of somatic pairing (Maguire 1967), or RIP and MIP gene inactivation processes in Neurospora (Selker 1990) and Ascobolus (Rhounim et al 1992), respectively. A genome-wide DNA/DNA homology search mechanism involving paranemic interactions has been suggested for all these phenomena (Rossignol & Faugeron 1994;Kleckner & Weiner 1993).…”
Section: Trans Control Of Dsbssupporting
confidence: 82%
“…The present results can be related to the observation in higher eucaryotes of somatic pairing (Maguire 1967), or RIP and MIP gene inactivation processes in Neurospora (Selker 1990) and Ascobolus (Rhounim et al 1992), respectively. A genome-wide DNA/DNA homology search mechanism involving paranemic interactions has been suggested for all these phenomena (Rossignol & Faugeron 1994;Kleckner & Weiner 1993).…”
Section: Trans Control Of Dsbssupporting
confidence: 82%
“…For the marks on transgenes, and transposable elements, the rate of change is very variable and dependent on environmental and developmental conditions (Mittelsten Scheid, 1995;Jorgensen, 1995). In some cases it has been found that once a transgene or a repeated gene has become repressed by heavy methylation, it is very difficult to re-activate it (Hadchouel et al, 1987;Allen et al, 1990;Rhounim et al, 1992). Often the extent of trans-generational stability of epigenetic marks is unknown, because it has been followed for only a limited number of generations: the induced dwarfism and lowered level of methylation found by Sano et al (1990) in rice was stable for the three generations it was studied, and the induced changes in the phenotype and level of methylation in Triticale were stable for three generations (Heslop-Harrison, 1990); the changed Y chromosome that affected variegation in Drosophila was examined and was stable for 11 generations (Dorn et al, 1993).…”
Section: How Stable Are Heritable Epigenetic Variations?mentioning
confidence: 99%
“…Based on data from MIP in Ascobolus (Rhounim et aL, 1992) and RIP in Neurospora (Selker, 1991), it has been hypothesized that the initial event that ultimately leads to suppression might be an interaction between homologous DNA loci (reviewed by Jorgensen, 1992Jorgensen, , 1993Matzke and Matzke, 1993). This then would promote DNA methylation and promoter inactivation.…”
Section: Interactions Between Transgenes and Homologous Resident Genesmentioning
confidence: 99%